Investigação empírica sobre os elementos para a medição de desempenho em sustentabilidade social - Carneiro, Mariana Pereira (2017)
The implementation of sustainable practices has been driving changes in business performance measurement systems, raising opportunities and challenges. Following the Triple Bottom Line concept, this thesis addresses the social dimension of sustainability. The primary focus is the external social sustainability and the impact measurement of sustainable social practices. Thus, the aim is to propose elements of a structural framework for measuring the sustainable social performance. The theoretical propositions are based on a literature review that grounded the elements proposition. The framework links the elements of social objectives deployed from stakeholder demands identification, short and long-term social goals, social sustainability performance measures for measuring the impact, and measurement of internal and external aspects of social sustainability. The research design was the multiple case studies in companies with different level sustainable social practices. Empirical evidence from case studies support both the theoretical propositions and the proposition of elements for the social sustainability performance measurement. Such elements allow measuring the social impact of sustainable social practices and identifying the stakeholders' role in selecting the sustainable social performance measurement. Those results are the first step in both improving comprehension and proposing the elements to support the social performance measurement.